A reversible bistate joint nimply optical logic gate using photonic crystals. (1st November 2021) - Rajesh, A; Viswanathan, B; Nafisa, N
Abstract: In this work an optical reversible bistate joint NIMPLY (BJN) logic gate was designed using two-dimensional photonic crystals. The gate was designed using an asymmetrical waveguide with reference to a point defect introduced at the center of the structure. The desired logic functions were obtained in the forward and reverse state using the principle of interference of light. The defect rod radius and length of the waveguide using a line defect were chosen to introduce constructive and destructive interference of light. The BJN gate has a low footprint of 40.83 µ m 2 and the resonant wavelength was designed to be 1550 nm. The finite-difference time-domain method was used to attain the wave propagation and photonic bandgap for the proposed structure. The maximum contrast ratio of the reversible optical BJN gate in the forward and reverse states was found to be 25.11 dB and 24.86 dB, respectively.